Apparent diffusion coefficients of the five major metabolites measured in the human brain in vivo at 3 T - Deelchand, Dinesh K. (Magn Reson Med, 2017)
PURPOSE: To measure the apparent diffusion coefficients (ADC) of five main metabolites in the human brain at 3 T with PRESS and STEAM, avoiding measurement biases due to cross-terms. Cross-terms arise from interactions between slice-selection and spoiler gradients in the localized spectroscopy sequence and the diffusion gradients. METHODS: Diffusion-weighted spectra were acquired from the prefrontal cortex in 5 healthy subjects using STEAM (T(E)/T(M)/T(R)=21.22/105/3000 ms, b-values=0 and 3172 s/mm(2)) and PRESS (T(E)/T(R)=54.2/3000 ms, b-values=0 and 2204 s/mm(2)). Diffusion weighting was applied using bipolar gradients in three orthogonal directions. Post-processed spectra were analyzed with LCModel, and the trace/3 ADC values were calculated. RESULTS: Comparable trace/3 ADC values (0.14–0.18 µm(2)/ms) were obtained for five main metabolites with both methods. These metabolites were quantified with Cramer-Rao lower bounds below 15%. CONCLUSION: The ADC values of the five main metabolites were successfully measured in the human brain at 3 T with eliminated directional dependence. Both STEAM and PRESS can be used to probe the diffusivity of metabolites in normal brain and various pathologies on the clinical scanner with slightly higher precision achieved with STEAM for glutamate and myo-inositol.